Clinical response and safety of malathion shampoo for treatment of head lice in a primary school - Siriwan Wananukul (2018)
Objective: Help eradicate or at least alleviating head lice in a primary school with malathion shampoo and to study clinical response and safety of malathion shampoo. Material and Method: All students were examined by using a fine-toothed lice comb to help detect live lice. Direct visual examination and the collection of nits for microscopic examination were performed to differentiate viable nits from empty nits. Diagnosis of head lice was made by the presence of lice. All students that had lice and/or nits were treated with malathion shampoo. Malathion shampoo was also provided for all family members. Pediculocidal efficacy was by the presence or absence of live lice. Blood for red blood cell cholinesterase activity was drawn in 32 volunteers before treatment and after the second treatment. Results: At the first visit, 629 students were examined and 48 students had live head lice. The infestation rate was 13% in girls and 1.3% in boys. The cure rate was 93% after the first treatment. The reported side effects were nausea, a burning sensation, and irritation that was found in five (4%), 10 (7%) and three (2%) students respectively. The mean of RBC cholinesterase activity before and after two applications showed significant changes (p = 0.03). It was -7.5 ± 4.1% reduction from the initial, but all were in the normal range. There was no report of clinical manifestation of malathion toxicity. Conclusion: Malathion shampoo is safe and effective in the treatment of head lice. There is significant skin absorption so a scalp examination for head lice should be done before subsequent application to avoid unnecessary exposure.